A home for friendless women - Hill, Kelly, 1979- (Vintage Books, 2024)
"In Victorian-era Louisville, when a woman finds herself unexpectedly pregnant, the Home for Friendless Women is the best - and only - place to go. Funded by wealthy Christian benefactors and managed by a firm hand, the Home has one missiong: to reform the 'fallen' women who live there into pious mothers and wives through religious lessons and hard work. For Ruth, a college student who's expelled after being raped on campus, the Home is a purgatory to endure before she can get her life back. For Belle, a queer sex worker who exchanged her bed at a brothel for one in the Home, it's a safe place to rest her feet until she can track down her missing lover. And for Minnie, the daughter of the religious couple who founded the charity, the Home is her mother's idea of a cautionary tale. But as Minnie prepares for the Home's silver anniversary party, she finds herself questioning the true cost of good intentions - and grappling with a terrible secret that has the power to unravel the Home entirely." -- page 4 of cover.